PENYULUHAN WASPADA HUBUNGAN TOXIC PADA REMAJA - Setyawati, Irni; Utami, Kusniyati; Ariendha, Dian Soekmawaty Riezqy (Stikes Yarsi Mataram, 2025)
Inkes Yarsi Mataram is one of the private health universities in West Nusa Tenggara (NTB) province that attracts teenagers from both inside and outside Lombok island. Adolescents who are away from parental supervision are more likely to have risky dating behaviour than students who live with their parents. From the results of research conducted in March 2024 on Inkes Yarsi Mataram students, it showed concerns about negative dating behaviour. Based on these problems, community service activities are needed in the form of counseling which includes pretesting adolescents' knowledge and attitudes, providing education through counseling and discussion about toxic relationships in adolescents conducted for two meetings, and ending with a post-test evaluation. After the counselling was carried out during April-May 2025, it was found that there was an increase in students' knowledge and attitudes after being given counselling on toxic teenage relationships. There needs to be a continuation of service by strengthening Islamic material as a form of implementation of Inkes Yarsi Mataram's goal of producing health workers who are morally good.